Accelerating carbon neutrality in Chinese cities: sensitive intervention points for the energy supply and demand sectors of Beijing and Hong Kong - Chung, SY (2021)
To limit the detrimental impacts of climate change, large-scale and rapid decarbonisation is required. China announced the plan to peak carbon emission before 2030 and to reach neutrality by 2060, which is faced with challenges posed by the energy sector including rising energy consumption and historical coal-based electricity generation. To complement the rigorous research being undertaken on the national neutrality trajectory, this research focuses on subnational carbon neutrality pathways with for two leading Chinese cities: Beijing and Hong Kong.